2022
DOI: 10.1002/mc.23452
|View full text |Cite
|
Sign up to set email alerts
|

Gender‐based effect of absence of gut microbiota on the protective efficacy of Bifidobacterium longum‐fermented rice bran diet against inflammation‐associated colon tumorigenesis

Abstract: Dietary rice bran (RB) has shown capacity to influence metabolism by modulation of gut microbiota in individuals at risk for colorectal cancer (CRC), which warranted attention for delineating mechanisms for bidirectional influences and cross‐feeding between the host and RB‐modified gut microbiota to reduce CRC. Accordingly, in the present study, fermented rice bran (FRB, fermented with a RB responsive microbe Bifidobacterium longum), and non‐fermented RB were fed as 10% w/w (diet) to gut microbiota‐intactspf o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(18 citation statements)
references
References 50 publications
2
14
0
Order By: Relevance
“…Silva-Reis R et al found that Blautia was with high abundance when dimethylhydrazine induced colorectal carcinogenesis [57]. But Kumar R et al considered that the enrichment of Blautia was correlated with anti-CRC e cacy of dietary rice bran [74]. Increasing abundance level of Eubacterium also was associated with anti-CRC e cacy of berberine [75].…”
Section: Discussionmentioning
confidence: 99%
“…Silva-Reis R et al found that Blautia was with high abundance when dimethylhydrazine induced colorectal carcinogenesis [57]. But Kumar R et al considered that the enrichment of Blautia was correlated with anti-CRC e cacy of dietary rice bran [74]. Increasing abundance level of Eubacterium also was associated with anti-CRC e cacy of berberine [75].…”
Section: Discussionmentioning
confidence: 99%
“…The methods of this study have been previously published [ 17 ]. Six-week-old male BALB/c mice ( n = 40) (Charles River Laboratories, Wilmington, MA, USA) were housed in an animal facility at The University of Colorado Denver-AMC, fed a control AIN-93M pellet diet, and acclimatized for 1 week.…”
Section: Methodsmentioning
confidence: 99%
“…Whole grain brown rice and rice bran contain unique bioactive phytochemicals, vitamins, and prebiotics that have exhibited the control and prevention of several types of human cancers [ 10 , 11 , 12 , 13 ], including colorectal cancer in both animals and humans [ 14 , 15 , 16 , 17 , 18 , 19 ]. Rice bran is the nutrient-rich outer layer of rice milled off to yield white rice.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations